Applicability of eddy current testing in CFRP using electrodes on CFRP surface and control of the testing range. (3rd September 2022) - Matsunaga, Wataru; Mizukami, Koichi; Mizutani, Yoshihiro; Todoroki, Akira
Abstract : In this study, a novel eddy current testing (ECT) method was developed to facilitate the testing of unidirectional carbon fiber reinforced plastic (UD-CFRP) and control the detection range. First, the effect of adding electrodes orthogonal to the fibers of UD-CFRP were analyzed. The results showed that the eddy current density could be significantly increased by adding electrodes. Moreover, it was found that the distribution of eddy current density in depth axis can be controlled by adjusting the distance of electrodes. Next, the same analysis was conducted for quasi-isotropic CFRP for comparison. The results showed that, unlike the results for the UD-CFRP, the distribution in depth direction could not be controlled by adjusting the distance of the electrodes. Finally, the impedance of the UD-CFRP with electrodes was measured, for confirming that adding electrodes facilitated ECT. It was also confirmed that the impedance increased as the distance between electrodes increased, and this trend was consistent with the numerical simulation results.